Beneficial effects of transfusing a patient with nontransfusion-dependent thalassaemia major. Issue 6 (June 1976) - McIntosh, N
Abstract : A case of nontransfusion-dependent thalassaemia major is presented showing growth retardation, recurrent fractures, late onset of puberty, deafness, and endocrine impairment of pancreas and adrenal gland. Regular blood transfusion to maintain mean haemoglobin at about 11 g/de improvedd all these problems. It is suggested that this improvement was related to improve tissue oxygenation.